2021
DOI: 10.29393/chjaas37-5frsm50005
|View full text |Cite
|
Sign up to set email alerts
|

FITOHORMONAS REDUCEN DAÑOS POR Nacobbus aberrans EN TOMATE (Solanum lycopersicum L.)

Abstract: Existen antecedentes de la reducción de daños por nemátodos con el uso de elicitores, compuestos que estimulan defensas en las plantas, promoviendo el metabolismo secundario. Este trabajo tuvo como objetivos evaluar la nematofauna presente en el suelo y raíces del cultivo antecesor, y medir el efecto sobre el rendimiento y daño en raíces por Nacobbus aberrans en tomate (Solanum lycopersicum)'Elpida', tratado por drench 24 horas previas al trasplante con 1 mL de ácido salicílico 0,50 x 10 -4 M y 1,00 x 10 -4 M,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…In addition, the hormone effect as elicitors of resistance to Nacobbus s.l. was corroborated by a significantly lower number of galls, gall index, nematode reproduction and increased the total yield of tomato plants, with salicylic acid being the most effective (10 -4 M) ( Martinez et al., 2021 ).…”
Section: Sustainable Strategies For Managementmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, the hormone effect as elicitors of resistance to Nacobbus s.l. was corroborated by a significantly lower number of galls, gall index, nematode reproduction and increased the total yield of tomato plants, with salicylic acid being the most effective (10 -4 M) ( Martinez et al., 2021 ).…”
Section: Sustainable Strategies For Managementmentioning
confidence: 90%
“…for resistance to M. incognita , showed that the application of exogenous hormones affects plant defenses by inducing changes on the nematode performance (invasion, damage and reproduction). Recently, 2021 ; Martinez et al. (2020 ) reported the impact of the exogenous application of hormones on tomato defenses from N. aberrans s.l.…”
Section: Sustainable Strategies For Managementmentioning
confidence: 99%
“…Al inicio del ensayo, el suelo se encontraba naturalmente infestado de N. aberrans, donde se encontró un número significativamente mayor a Dorylaimus spp. (Martínez et al, 2021).…”
Section: Introductionunclassified